2003
DOI: 10.2320/matertrans.44.1647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Titanium on Glass-forming Ability of Cu-Zr-Al Alloys

Abstract: The effect of partial substitution of Ti for Zr on the glass-forming ability was studied in Cu 50 Zr 45Àx Ti x Al 5 (x ¼ 0, 2.5, 5, 10) alloys by using thermal analysis and X-ray diffractometry. The glass transition temperature, T g , of Cu 50 Zr 45Àx Ti x Al 5 alloys decreased from 707 K at x ¼ 0 to 700 K at x ¼ 2:5, and keeps almost constant with further increase of x. On the other hand, the crystallization temperature, T x , decreased gradually from 767 K at x ¼ 0 to 741 K at x ¼ 10. The partial substitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The Young's modulus (E), fracture strength (σ cf ) and compressive yielding strength (σ cy ) are 59 GPa, 850 and 904 MPa respectively, which are higher than those of the Mg 65 Cu 25 Gd 10 alloy. It is noted that such good mechanical properties for the Mg-based BMGs have not been reported hitherto [4,9,10]. The compression tests of the Mg-Cu-Gd bulk metallic glass showed no evidence of plastic yielding before fracture, possibly due to the embrittlement result from the structural relaxation at room temperature [11].…”
Section: Resultsmentioning
confidence: 99%
“…The Young's modulus (E), fracture strength (σ cf ) and compressive yielding strength (σ cy ) are 59 GPa, 850 and 904 MPa respectively, which are higher than those of the Mg 65 Cu 25 Gd 10 alloy. It is noted that such good mechanical properties for the Mg-based BMGs have not been reported hitherto [4,9,10]. The compression tests of the Mg-Cu-Gd bulk metallic glass showed no evidence of plastic yielding before fracture, possibly due to the embrittlement result from the structural relaxation at room temperature [11].…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] More recently, it has been shown that the substitution of yttrium by gadolinium could also improve the GFA of ternary compositions. [5] For such alloys, fracture strengths higher than 800 MPa have been obtained in compression. [6] The same interesting effect of the substitution of the rare earth (RE) was also observed on the quaternary compositions containing Ag which shows improved fractures stress and some limited plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…For Ni-Fe-B MGs, it has been shown theoretically [48] and experimentally [49][50][51][52] The partial substitution of Cu by Ag and Pd improves the GFA of the Mg65Cu25Gd10 ternary alloy. The Mg65Cu15Ag5Pd5Gd10 BMG sample 10 mm in diameter is fabricated by a conventional Cu-mold casting method in air atmosphere [53]. Fig.…”
Section: Mg-based Bmgsmentioning
confidence: 99%